(3GdeLehYI GdCOHjIs - (3eLehYI ef GdeDdajfs ((3GdbSWfWjfjI s)
(3ChdgG (B:s
(3LeYJ ai gPg GdChQGb eG UGOaJg ai cJH GdCOH ef GdCTYGQ GdLjOI Ydi WQjb GdeShOI HfGA efi Cf CfJNH efgG HYO Pdc CHdZgG eYfi hCaUMgG daXkG s
(3BNQgG (B:s
(3heeG CfTOfjI HYV GdCOHGA ai GdbSWfWjfI be HfG jG fhQ Yjfi fLYd GdTc jbjfG aEdi ce jG MHjHi HCKe GdbGFd ajfG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs